Injuries in basketball and its environmental causes - Ahmet Gursel Oguz; Oksay Oguz (Türk Spor ve Egzersiz Dergisi)
Sports injuries is the collective name of all kinds of damage occurring during sports activities. injury is caused by internal and external influences, it makes functional abnormalities on tissues partially or fully. There are general rules can be applied to all kind of sports which can reduce injuries. Sport science shows that injuries can be reduce 25% in condition that all precautions are taken. Each sport has their specific forms of training, technical components and elements which are affecting people. Internal and external factors that lead to sports injuries; varies according to each sports property. The presence of these factors are affecting performance. Even the presence of the audience today may lead sport injuries. Sport injury factors are internal and external factors. Our study is on external factors literature and data.